Perkiraan Dampak Kebijakan Proteksi dan Promosi terhadap Ekonomi Hortikultura Indonesia - nFN Saptana; Prajogo Utomo Hadi (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2008)
EnglishTrade liberalization and economic crisis generate greater challenges in agricultural development in Indonesia. Despite the remaining high tariff rate on Indonesian agricultural products as stated in the WTO agreement, this country applied low import tariff rates of 0-5% during the 1998–2004 for almost all its agricultural products, except for rice and sugar which are increased to 25-30%. Since 1 January 2005, Indonesia applies higher tariff rates of 10-40% for a number of agricultural products, including horticultural products. Indonesia also launches policies to promote development of horticultural sector. This paper aims to analyze the impact of protection as well as promotion policies on horticultural economy both at macro and micro level. It is found that he protection policy in terms of increasing tariff rates from 5% to 25% for shallots and oranges would potentially increases wholesale price, producer price, production quantity, producer surplus and farm income, but reduces demand/ consumption, consumer surplus, import and government revenue from import tax. Impact of promotion policy in terms of improved distribution system if the subsidized fertilizers potentially reduces fertilizer cost by Rp 1.37 million for potato farm in Karo (North Sumatera), Rp 0.44 million for potato farm in Tabanan (Bali), and Rp 0.21 million for shallots farm in Majalengka (West Javat) per hectare per season, and by Rp 4.03 million for orange farm in Karo and Rp 1.56 million for mango farm in Majalengka per hectare per year. Meanwhile, import relaxation for potato seeds of french fries and Atlantic varieties is expected to increase production and export of processed products of potato. The future policy perspectives would be maintaining the existing tariff and promotion policies as well as deregulation and de-bureaucratization inclined towards the improved competitiveness of horticultural products and farmer’s income. IndonesianLiberalisasi perdagangan dan krisis ekonomi menimbulkan tantangan yang semakin berat dalam pembangunan sektor pertanian di Indonesia. Meskipun komitmen tarif produk pertanian Indonesia dalam forum WTO masih cukup tinggi, selama kurun waktu 1998–2004 Indonesia menerapkan tarif impor 0-5 persen untuk hampir semua produk pertanian, kecuali beras dan gula yang dinaikkan menjadi 25-30 persen. Baru pada tanggal 1 Januari 2005, Indonesia mulai menerapkan kebijakan tarif relatif tinggi (10-40%) untuk beberapa produk pertanian termasuk hortikultura. Indonesia juga menempuh kebijakan promosi untuk pengembangan subsektor hortikultura. Tulisan ini bertujuan mengkaji dampak kebijakan proteksi dan kebijakan promosi terhadap ekonomi komoditas hortikultura di tingkat makro dan mikro. Dampak kebijakan proteksi berupa peningkatan tarif impor dari 5 persen menjadi 25 persen untuk bawang merah dan jeruk berpotensi meningkatkan harga grosir, harga petani, produksi, surplus produsen, dan pendapatan usahatani, tetapi mengurangi konsumsi, surplus konsumen, impor, dan penerimaan pemerintah dari pajak. Dampak kebijakan promosi berupa perbaikan sistem distribusi pupuk berpotensi menurunkan biaya pupuk per hektar per musim pada usahatani kentang di Karo (Sumatera Utara) dan Tabanan (Bali), masing-masing Rp 1,37 juta dan Rp 0,44 juta, usahatani bawang merah di Majalengka (Jawa Barat) Rp 0,21 juta, usahatani jeruk di Karo (Sumatera Utara) Rp 4,03 juta, dan usahatani mangga di Majalengka (Jawa Barat) Rp 1,56 juta. Sementara itu, pelonggaran impor bibit kentang varietas french fries dan Atlantik diharapkan akan meningkatkan produksi dan ekspor hasil olahan keripik kentang. Perspektif kebijakan ke depan adalah mempertahankan kebijakan tarif dan promosi, serta kebijakan deregulasi dan debirokratisasi yang di arahkan untuk meningkatkan daya saing produk hortikultura nasional dan pendapatan petani.